Developmental trajectories of emotional disengagement from schoolwork and their longitudinal associations in England. (26th August 2016) - Symonds, Jennifer; Schoon, Ingrid; Salmela‐Aro, Katariina
Abstract : This study identified the varied ways in which emotional disengagement from schoolwork typically developed between 14 and 16 years of age, in the Longitudinal Study of Young People in England. Using growth mixture modelling we found eight main trajectories of (dis)engagement, with four trajectories of either increasing or stable emotional disengagement with schoolwork (41% of the sample). Using propensity score matching to create groups balanced on a wide range of covariates at Wave 1, we compared disengaged students to their engaged counterparts to identify the longitudinal effects of disengagement‐trajectory membership on behavioural engagement, psychological wellbeing, substance use, career pathways and achievement. Using linear and binary logistic regressions, we established that students in disengagement trajectories developed lower achievement across compulsory secondary school, and participated less in education and more in employment at age 17 years. In young adulthood (age 19–20 years) they were less likely to attend university and more likely to be unemployed. During secondary schooling, they developed higher levels of substance use and poorer psychological wellbeing, which persisted in the year after compulsory school. However, in young adulthood, the differences in substance use dissipated and students in most of the disengagement trajectories had relatively similar life satisfaction to their counterparts. These findings suggest that students (except perhaps those who became unemployed) were able to develop healthily and happily after leaving the schoolwork environments from which they were emotionally disengaged.